Integrity management and the public service ethos in the UK: patchwork quilt or threadbare blanket? - Heywood, Paul M. (2010)
This paper focuses on the nature of integrity management in contemporary UK public life. Despite traditionally high standards of integrity in the public service, it has recently been argued that the UK’s National Integrity System resembles a patchwork quilt of poorly defined institutional roles, questionable independence, and contested notions of how best to disseminate and uphold ethical practice. The paper traces how a relatively enduring characteristic known as the British public service ethos (PSE), which places emphasis on informal codes of conduct and moral integrity, has evolved within broader systemic changes to the style of public service delivery. It is argued that pressures to decentralise public service delivery sit in tension with, and feed into, piecemeal attempts to centralise and codify integrity management. This dynamic is presented in terms of the tension between a compliance-based and a values-based approach to integrity management.